1997
DOI: 10.1103/physrevlett.78.2752
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Realization of Second Harmonic Generation in a Fibonacci Optical Superlattice of LiTaO3

Abstract: We have designed and fabricated a novel nonlinear optical superlattice of LiTaO 3 in which two antiparallel 180 ± domains building blocks A and B were arranged as a Fibonacci sequence. We measured the quasi-phase-matched second-harmonic spectrum of the superlattice. The second-harmonic blue, green, red, and infrared light generation, with energy conversion efficiencies of ϳ5% 20%, was demonstrated experimentally, which efficiencies are comparable with those of a periodic superlattice. Destruction of self-simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
116
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(118 citation statements)
references
References 11 publications
0
116
0
2
Order By: Relevance
“…The concept of Quasi-phase-matching 4,7,8 has been realized in such periodic and quasi-periodic superlattices to achieve harmonic generations and other nonlinear processes with high efficiency. [8][9][10][11][12][13][14][15][16][17][18] The schematic configuration of superlattice is displayed in Fig. 1.…”
mentioning
confidence: 99%
“…The concept of Quasi-phase-matching 4,7,8 has been realized in such periodic and quasi-periodic superlattices to achieve harmonic generations and other nonlinear processes with high efficiency. [8][9][10][11][12][13][14][15][16][17][18] The schematic configuration of superlattice is displayed in Fig. 1.…”
mentioning
confidence: 99%
“…Both periodic and quasi-periodic nonlinear structures have been studied primarily with the aim of improving harmonic generation efficiency. QPSs with additional degrees of freedom due to the higher order group symmetry are particularly attractive for creating higher density of states that can facilitate harmonic generation [36][37][38]. It has been observed in [25] that the efficiency of second-harmonic generation (SHG) in QPS is higher than in random medium, but still remains lower than in regular periodic structures.…”
Section: Open Accessmentioning
confidence: 99%
“…In fact, a QP multilayer can provide more reciprocal vectors to the quasi-phase-matching optical process, and this ultimately results in a more plentiful spectrum structure than that of a periodic multilayer. 29 The importance of the role played by the quasiperiodicity of the substrate is further highlighted when considering third-harmonic generation, where it has been shown that the conversion efficiency in a QP multilayer is increased by a factor of 8 in comparison with the two-step process required for a third-harmonic generator constructed by two periodic superlattices. 30 Quite interestingly, the possibility of designing Fibonacci-based structures able to simultaneously phase match any two nonlinear interactions by introducing a QP modulation of the nonlinear coefficient in ferroelectric devices has been recently discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] This interest has motivated several theoretical works aimed to understand the interplay between the optical properties and the underlying aperiodic order of the system through the study of exciton optical absorption 27 and fluorescence decay in aperiodic lattices. 28 At the same time, new insights into the optical capabilities of aperiodically ordered systems have been recently demonstrated by a number of experimental achievements, involving second- 29 and third-harmonic generation, 30 as well as the possible localization of light waves in FDM's. 31,32 Underlying all these theoretical and experimental efforts a crucial fundamental question remains concerning whether quasiperiodically ordered devices would achieve better performance than usual periodic ones for some specific applications.…”
Section: Introductionmentioning
confidence: 99%